Understanding Aquaporin Transport System in Eelgrass (Zostera marina L.), an Aquatic Plant Species - Shivaraj, S. M.; Deshmukh, Rupesh; Bhat, Javaid A.; Sonah, Humira; Bélanger, Richard R. (Frontiers in Plant Science, 2017)
Aquaporins (AQPs) are a class of integral membrane proteins involved in the transport of water and many other small solutes. The AQPs have been extensively studied in many land species obtaining water and nutrients from the soil, but their distribution and evolution have never been investigated in aquatic plant species, where solute assimilation is mostly through the leaves. In this regard, identification of AQPs in the genome of Zostera marina L. (eelgrass), an aquatic ecological model species could reveal important differences underlying solute uptake between land and aquatic species. In the present study, genome-wide analysis led to the identification of 25 AQPs belonging to four subfamilies, plasma membrane intrinsic proteins (PIPs), tonoplast intrinsic proteins (TIPs), nodulin26-like intrinsic proteins (NIPs), small basic intrinsic proteins (SIPs) in eelgrass. As in other monocots, the XIP subfamily was found to be absent from the eelgrass genome. Further classification of subfamilies revealed a unique distribution pattern, namely the loss of the NIP2 (NIP-III) subgroup, which is known for silicon (Si) transport activity and ubiquitously present in monocot species. This finding has great importance, since the eelgrass population stability in natural niche is reported to be associated with Si concentrations in water. In addition, analysis of available RNA-seq data showed evidence of expression in 24 out of the 25 AQPs across four different tissues such as root, vegetative tissue, male flower and female flower. In contrast to land plants, higher expression of PIPs was observed in shoot compared to root tissues. This is likely explained by the unique plant architecture of eelgrass where most of the nutrients and water are absorbed by shoot rather than root tissues. Similarly, higher expression of the TIP1 and TIP5 families was observed specifically in male flowers suggesting a role in pollen maturation. This genome-wide analysis of AQP distribution, evolution and expression dynamics can find relevance in understanding the adaptation of aquatic and land species to their respective environments.